Identifikasi Polimorfisme Gen CYP1A1 pada Karsinoma Sel Skuamosa dan Adenokarsinoma Serviks - Delyuzar; Hidayat; Hilda Fitriyani (Majalah Patologi Indonesia, 2020)
BackgroundCervical cancer is the third most common cancer in women with risk factor of smoking, high parity, long term use of oralcontaception that are associated with chemical carcinogenesis. Chemical carcinogenesis require biotransfor-mation of lipophilicsubstrates to hydrophilic metabolites, therefore facilitating their secretion from the human body. Cytochrome P450 (CYP) is one ofgenes that have important role in this process. Benzo[α]pyrene and estrogen have a common biotransformation process which ismetabolized by CYP, particularly CYP1A1. The objectives to identify the frequency and distribution of CYP1A1 gene polymorphismin squamous cell carcinoma and adenocarcinoma of the cervix.MethodsThis is an analytical descriptive study with cross sectional approach. CYP1A1 gene polymorphism (3801T/C or Ile462Val) wasanalyzed using PCR-RFLP method followed by gel electrophoresis.ResultsCYP1A1 gene polymorphisms (3801TC) in squamous cell carcinoma were 50% heterozygote T/C, 36% wild-types T/T and 14%homozygote C/C. CYP1A1 gene polymorphisms (3801TC) in adenocarcinoma were 60% heterozygote T/C and 40% wild-types T/T.CYP1A1 gene polymorphisms (Ile462Val) in squamous cell carcinoma were 97.2% heterozygote Ile/Val, and 2.8% homozygoteVal/Val. CYP1A1 gene polymorphisms (Ile462Val) in adenocarcinoma were 100% heterozygote Ile/ValConclusionThe most common type of CYP1A1 gene polymorphism (3801TC and Ile462Val) in squamous cell carcinoma and adenocarcinomaof the cervix were heterozygote.